Ekhomorfofunkktsionalnye "markery" energeticheskogo obmena v miokarde u sportsmenov - predstavitelej tsiklicheskikh vidov sporta - Kachan, J. V.; Nechaeva, G. I.; Rozhdestvenskij, M. E.; Smitienko, O. L. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The purpose of this research was to study the indirect morphofunctional parameters of the power exchange in a myocardium with the use of echocardiography (EchoCG) and stresses of myocardium walls in athletes. It was surveyed 120 athletes (80 men and 40 women) aged 16-22 years engaged in cyclic kinds of sports: swimming (n=15), ski races (n=18), track and field athletics (n=29), cycling (n=18) and speed skating (n=14). The sports qualification of athletes was masters and candidates in the master of sports. The group of comparison consisted of 120 people of the same age and gender, which were not engaged in sports trainings. The complex of methods including intervalcardiography, ultrasonic research of the heart by methods of EchoCg and dopplerechocardiography was used in the research. The observably at the majority of the surveyed athletes deregulation between vagotonic and sympathetic parts of innervation specified the change of the restoration of the power processes in a myocardium which determined the power and an orientation kinetics and restoration of power processes in a heart. The display of disintegration was expressed in the mismatch of correlation connections between separate parameters of hemodynamics, that has forced a heart to work in the inadequate and the hard regime. The absence of the reorganization of mechanisms of the adaptation of a heart has created the conditions close to its overstrain that could promote the development of the dystrophic changes of a myocardium.